ANALISIS KETAHANAN PANGAN RUMAH TANGGA MISKIN DI KABUPATEN SUMBAWA - Kamaruddin, K; Putri, Mega Pelangi (Jurnal Ekonomi & Bisnis, 2025)
This study aims to analyze food security in poor households in Penyaring Village, Moyo Utara sub-district. The type of this study was associative study. The data used was primary data. The numbers of population in this study were 209 poor household families. The technique used of determining sampling was Arikunto formula, thus the number of samples were 32 poeple. The tool used to collect data was through questionnaire. The data analysis tool used was multiple linear regression. The results of the study showed that partially food availability had a positive and significant effect on the food security of poor households, food stability had a positive and significant effect on the food security of poor households, food accessibility had a positive and significant effect on the food security of poor households, food quality had a positive and significant effect on the food security of poor households. Then simultaneously food availability, food stability, food accessibility, and food quality had a significant effect on the food security of poor households. The ability of food availability, food stability, food accessibility and food quality to effect variations in changes on the food security of poor households in Sumbawa District was 48.3%, while the remaining 0f 51.7% was effected by other variables outside this research model, such as the number of family members, household income, household expenditure and education level.